Further modelling of LADM's rights, restrictions and responsibilities (RRRs). (December 2015) - Paasch, Jesper M.; van Oosterom, Peter; Lemmen, Christiaan; Paulsson, Jenny
Highlights: Modelling of LADM's RRRs based on the Legal Cadastral Domain Model and Social Tenure Domain Model. A specialized description of RRRs in the LADM may be of future value for social tenure land use. Focus on expanded RRR code tables. Need of maintenance of expanded RRR code tables. Abstract: This paper proposes a more detailed classification of the legal part of the Land Administration Domain Model (LADM), ISO 19152 (i.e. interests in land), than described in the current standard by further developing the LADM's 'right', 'restriction' and 'responsibility' (RRR) class and associated code lists. Besides the more obvious formal right descriptions, this paper also deals with informal rights' descriptions as introduced in the Social Tenure Domain Model (STDM) as a foundation for further LADM development. The authors base their research on the Legal Cadastral Domain Model, as developed by and described in the Ph.D. thesis of Paasch, which is used as a conceptual basis for adding an additional level to the LADM. Interests in land can be classified in this model as limiting or beneficial to real property ownership. The extended classification is further based on the paradigm that there are two major types of interest in land, privately agreed interests and regulations imposed by a public agency. The incorporation of a specialized classification of RRRs in the LADM is of value for more inclusion of social tenure in (inter-)national land administration registers. The LADM allows national profiles to be added to the standard, however, such profiles are relevant within a country. These profiles are needed in cases where detailed data of interests in land have to be exchanged internationally. International data exchange requires maintenance of code tables representing the different RRRs in use within countries. OICRF has announced an initiative in support to this.